Efficacy of laboratory prepared wettable powder formulation of entomopathogenous fungi Beauveria bassiana, Metarhizium anisopliae and Paecilomyces fumosoroseus against the Polyphagotarsonemus latus (Bank) (Acari: Tarsonemidae) (broad mite) on Capsicum annum (chilli) - Nugroho, Ihsan; Ibrahim, Yusof (Penerbit Universiti Sains Malaysia, 2007)
The efficacies of wettable powder (WP) formulations of Beauveria bassiana (BbGc), Paecilomyces fumosoroseus (PfPp) and Metarhizium anisopliae (MaPs) as a single or combined treatments against the Polyphagotarsonemus latus (Bank) (Acari: Tarsonemidae) (broad mite) and its damage on one month old Capsicum annum (chilli) plants were compared with the acaricide amitraz in the field. The WP formulations were applied at four spray intervals on the chilli shoots at the rate of 1 × 1010 conidia ml-1. Both B. bassiana and P. fumosoroseus significantly reduced the mite population and subsequently resulted in a high percentage of shoot recovery by the fourth spray compared with the control. Combined treatments of M. anisopliae and P. fumosoroseus, and M. anisopliae and B. bassiana could not adequately suppress mite population hence comparatively more shoots were infested. New shoots treated with B. bassiana resulted in excellent recovery (93.33% shoot protection) which was not significantly different from that of amitraz (96.67%). Amitraz could suppress the mite population faster whereby zero level of mite population was achieved after the second spraying. Nevertheless, WP formulation of B. bassiana as a miticide was as effective as amitraz against the broad mites.